1986
DOI: 10.1093/jn/116.9.1640
|View full text |Cite|
|
Sign up to set email alerts
|

Urea Cycle Activity and Arginine Formation in Rainbow Trout (Salmo gairdneri)

Abstract: Studies were conducted to determine whether rainbow trout fingerlings possess the ability to synthesize arginine via the urea cycle. Several urea cycle enzymes were detected in trout tissues. An experiment was conducted to determine whether the enzymes increase in response to starvation or in response to dietary protein level (0, 30, 40, 50% protein). Although some effects were observed, they did not appear to be consistent with the function of the urea cycle as a mechanism of detoxifying ammonia in the fish. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…Chiu et al, 1986;Jürss et al, 1987). Although arginase activity per gram of liver tissue and per mg of liver protein significantly increased in fasted fish, if one considers enzyme activity per gram of fish, arginase activities are similar between fasted and fed fish (6·weeks).…”
Section: Upregulation Of Arginase With Fastingmentioning
confidence: 98%
See 3 more Smart Citations
“…Chiu et al, 1986;Jürss et al, 1987). Although arginase activity per gram of liver tissue and per mg of liver protein significantly increased in fasted fish, if one considers enzyme activity per gram of fish, arginase activities are similar between fasted and fed fish (6·weeks).…”
Section: Upregulation Of Arginase With Fastingmentioning
confidence: 98%
“…Chiu et al, 1986;Jürss et al, 1987). We hypothesized that the two trout arginase genes would be differentially regulated in response to dietary manipulation.…”
Section: Upregulation Of Arginase With Fastingmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Kaushik et al (1988) found that urea pathway accounted for less than 50% of arginine catabolism in rainbow trout. Different patterns of plasma urea production might result from the differences of fish food habits, living habits, or the ability to response to both dietary and environmental changes (Chiu et al, 1986;Twibell and Brown, 1997). Anyhow, plasma urea in response to dietary arginine, is less clear and further studies are needed to investigate not only the effects of dietary amino acid levels and/or balance but also the contribution of organs or tissues other than liver to urea production.…”
Section: Tablementioning
confidence: 99%